Association between ambient air pollutants and short-term mortality risks during 2015–2019 in Guangzhou, China - Chen, Yuyang; Chen, Sili; Zhang, Lei; Kang, Weishan; Lin, Guozhen; Yang, Qiaoyuan (Frontiers in Public Health, 2024)
With the development of technology and industry, the problem of global air pollution has become difficult to ignore. We investigated the association between air pollutant concentrations and daily all-cause mortality and stratified the analysis by sex, age, and season.Data for six air pollutants [fine particulate matter (PM2.5), inhalable particles (PM10), nitric dioxide (NO2), sulfur dioxide (SO2), ozone (O3), and carbon monoxide (CO)]and daily mortality rates were collected from 2015 to 2019 in Guangzhou, China. A time-series study using a quasi-Poisson generalized additive model was used to examine the relationships between environmental pollutant concentrations and mortality. Mortality data for 296,939 individuals were included in the analysis. The results showed that an increase of 10 μg/m 3 in the concentrations of PM2.5, PM10, SO2, O3, NO2, and CO corresponded to 0.84% (95% confidence interval [CI]: 0.47%, 1.21%), 0.70% (0.44%, 0.96%), 3.59% (1.77%, 5.43%), 0.21% (0.05%, 0.36%), 1.06% (0.70%, 1.41%), and 0.05% (0.02%, 0.09%), respectively. The effects of the six air pollutants were more significant for male individuals than female individuals, the cool season than the warm season, and people 75 years or older than those younger than 75 years. PM2.5, PM10, SO2, and NO2 were all associated with neoplasms and circulatory and respiratory diseases. The twopollutant models found that PM2.5, PM10 and NO2 may independently affect the risk of mortality. The results showed that exposure to PM2.5, PM10 and NO2 may increase the risk of daily all-cause excessive mortality in Guangzhou.